Eksistensi Manajemen Pemasaran dalam Membangun Citra Lembaga Pendidikan - Toha Ma'sum (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2020)
Related to the image of schools and efforts to create a positive image, it cannot be separated from the efforts of the school, especially the public relations department. Public Relations in education have special tasks including: Evaluating public attitudes and opinions towards the organization, Formulation and implementation of organizational procedures and policies for organizational communication with the public, coordinating communication programs between organizations and the public, developing relationships through communication processes, developing attitudes and relationships positive between the organization and the public. As well as creating public perception and a good image for the institution. Marketing management education services can apply Marketing management theory including marketing planning, marketing organizing, marketing implementation / implementation, and marketing supervision. The effort to improve and maintain a positive image is an academic reputation / academic quality, and is aimed at improving the Quality of Education Services, improving Education Services Products, and adding other efforts in the form of building communication, implementing discipline, giving direction to alumni to maintain the good name of the alma mater. The existence of marketing education services in enhancing the image is that marketing education services is carried out by promoting excellent learning programs, positive activities outside of school, and by planning well-programmed programs. has succeeded in improving and maintaining the image of the school.